Effects of Desk-Bike Cycling on Phonological Working Memory Performance in Adolescents With Attention Deficit Hyperactivity Disorder - Ruiter, Margina; Görlich, Emma; Loyens, Sofie; Wong, Jacqueline; Paas, Fred (Frontiers in Education, 2022)
We investigated the effects of active workstations on cognitive control functions in individuals diagnosed with Attention Deficit Hyperactivity Disorder (ADHD). In a fully counterbalanced randomized control design, we examined the effects of cycling on a desk bike on phonological working memory (WM) in 18 adolescents with ADHD. Adolescents performed a phonological WM test across two separate sessions during which they either cycled or not. It was hypothesized that participants would perform better on the WM task while cycling as compared to seated-rest. Results showed that total WM performance was not affected by desk-bike cycling. Exploratory analyses suggested that cycling during more difficult trials (i.e., high WM demands) is beneficial for WM performance. More research is needed to shed light on how task difficulty moderates the potential compensatory effect of desk-bike cycling on WM performance in adolescent ADHD participants.